Durian seed meal for commercial layers: performance, nutrient retention and egg quality - Mangisah, I.; Ismadi, V. D. Y. B.; Sukamto, B.; Wahyono, F.; sugiharto, S. (Diponegoro University, 2020)
This study was conducted to evaluate diets containing durian (Durio zibethinus Murr) seed meal (DSM) on the performance, nutrient retention and egg qualities of commercial layers. A total of 120 fifty two -week-old laying hens were distributed according to a completely randomized design in four treatments and five replications with six birds each. The treatments consisted of different levels of durian seed meals (control, 3% DSM, 6% DSM, and 9% DSM). Feeding diets containing durian seed meal had no significant effect (p > 0.05) on the feed consumption of laying hens at 58 wk of age. Inclusion of up to 6% DSM in formulated layer diets did not reduce egg production and nutrient digestibility, but reduced egg weight. No differences (p>0.05) were observed in egg calcium content, egg calcium mass, and yolk color score fed diets containing DSM. This study suggests that DSM could be incorporated up to 6% in laying hen diets without adverse effect on production performance, nutrient retention and egg qualities.